2021
DOI: 10.1021/acsami.1c17904
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Resin Dual-Use Stamps for Capillary Stamping and Decal Transfer Printing

Abstract: We report an optimized two-step thermopolymerization process carried out in contact with micropatterned molds that yields porous phenolic resin dual-use stamps with topographically micropatterned contact surfaces. With these stamps, two different parallel additive substrate manufacturing methods can be executed: capillary stamping and decal transfer microlithography. Under moderate contact pressures, the porous phenolic resin stamps are used for nondestructive ink transfer to substrates by capillary stamping. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Stamps exhibiting continuous pore systems have been used for additive substrate patterning in automatized configurations and even under the extreme conditions of solvothermal syntheses . However, percolative transport of viscous mixtures containing polymers and additional components impeding flow, such as CNTs, through porous stamps might be too slow for efficient stamping procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Stamps exhibiting continuous pore systems have been used for additive substrate patterning in automatized configurations and even under the extreme conditions of solvothermal syntheses . However, percolative transport of viscous mixtures containing polymers and additional components impeding flow, such as CNTs, through porous stamps might be too slow for efficient stamping procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The direct deposition of patterns of solvothermal reaction products may be achieved by the coupling of solvothermal syntheses with in situ additive substrate patterning. It was shown that porous stamps are particularly suitable for parallel additive substrate patterning even if diluted precursor solutions are used as inks because the pore systems of the stamps act as ink reservoirs. Evaporation of the volatile ink components (typically the solvents) drags more and more of the nonvolatile ink components, such as precursors of solvothermal reaction products, into the liquid ink bridges formed between the contact elements of the stamp and the substrate to be patterned.…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment of the nonvolatile ink components in the liquid bridges is a crucial aspect of additive pattern formation with porous stamps . However, the porous stamps so far available are not compatible with solvothermal processes; polymeric stamps ,, are too deformable, whereas silica , and phenolic resin stamps are too brittle. In general, reactive additive lithography has, so far, predominantly been conducted with solid stamps under ambient pressure and temperature …”
Section: Introductionmentioning
confidence: 99%